Student-led sustainability transformations: employing realist evaluation to open the black box of learning in a Challenge Lab curriculum. Issue 8 (8th February 2021) - Holmén, Johan; Adawi, Tom; Holmberg, John
Abstract : Purpose: While sustainability-oriented education is increasingly placing importance on engaging students in inter- and transdisciplinary learning processes with societal actors and authentic challenges in the centre, little research attends to how and what students learn in such educational initiatives. This paper aims to address this by opening the "black box" of learning in a Challenge Lab curriculum with transformational sustainability ambitions. Design/methodology/approach: Realist evaluation was used as an analytical frame that takes social context into account to unpack learning mechanisms and associated learning outcomes. A socio-cultural perspective on learning was adopted, and ethnographic methods, including interviews and observations, were used. Findings: Three context-mechanism-outcome (CMO) configurations were identified, capturing what students placed value and emphasis on when developing capabilities for leading sustainability transformations: engaging with complex "in-between" sustainability challenges in society with stakeholders across sectors and perspectives; navigating purposeful and transformative change via backcasting; and "whole-person" learning from the inside-out as an identity-shaping process, guided by personal values. Practical implications: The findings of this paper can inform the design, development, evaluation and comparison of similar educational initiatives across institutions, while leaving room for contextual negotiation and adjustment. Originality/value: This paper delineates and discusses important learning mechanisms and outcomes when students act as co-creators of knowledge in a sustainability-oriented educational initiative, working with authentic challenges together with societal actors.